Análisis comparativo de los perfiles de expresión génica de células histiocíticas ante la exposición a LPS - Martinelli, Romina (2017)
The cellular arm of the innate immune response, consisting of mononuclear phagocytes and\ndendritic cells, plays an important role by initiating, directing and modulating different aspects of\nthe adaptive immune response. These cells, despite their phenotypic diversity, share essential\nfunctions to the development of the immune response.\nIn this work were used data from cells exposed to lipopolysaccharide (LPS), a glycolipidic\nmacromolecule present on the wall of Gram negative bacteria. This model allows to make\ninferences about different kinds of diseases in which inflammation plays an essential role. Here,\ndata from DNA microarray experiments of monocytes, macrophages and dendritic cells exposed\nto LPS were analyzed. By means of clustering techniques and functional enrichment analysis\nwas identified a group of over-expressed genes in the three cell types, including some that can\nmodulate the inflammation through the inhibition of NFkB pathway and that also can be\nregulated by calcitriol.\nThis results allowed us to construct a gene regulatory network model that can help to understand\nthe vitamin D antiinflammatory action, one of the non-classical actions of this compound. This\nalso opens the search for molecules that can act as therapeutic targets for a variety of diseases in\nwhich inflammation plays an important role during their pathogenesis